Influence of the Cellulose Purification Method on the Properties of PVA Composites with Almond Shell Fibres - Irene Gil-Guillén; Chelo González-Martínez; Amparo Chiralt (Molecules)
Almond shells (ASs) are a potential source of cellulose that could be obtained through sustainable methods for their valorisation. Biocomposites (BCs) from polyvinyl alcohol (PVA) and cellulose are interesting materials for developing sustainable packaging materials. BC based on PVA and AS cellulose were obtained by melt blending and compression moulding, by using subcritical water extraction at 160 or 180 °C, and subsequent bleaching with sodium chlorite (C) or hydrogen peroxide (P) to purify cellulose. The influence of the purification method on the properties of BC was analysed. Fibres treated with C were better dispersed in composites than those bleached with P. Residual phenolic compounds in the fibres provide the composite with ABTS∙+ scavenging capacity in line with the residual lignin content of the fibres. Both the presence of phenols and dispersed fibres reduced the film transparency, mainly in the UV range. Fibres enhanced the oxygen barrier capacity of composites, and those treated with HP also improved the water vapour barrier capacity. Fibres treated with C better promoted the increase in the elastic modulus of the composites, due to their highest crystallinity and dispersibility, while favoured the PVA crystallisation. Therefore, the obtained AS cellulose fibres could be used to obtain thermoprocessed PVA biocomposites for food packaging applications.